What caused seven consecutive years of low puerulus settlement in the western rock lobster fishery of Western Australia?. (19th October 2014) - de Lestang, Simon; Caputi, Nick; Feng, Ming; Denham, Ainslie; Penn, James; Slawinski, Dirk; Pearce, Alan; How, Jason
Abstract: Puerulus settlement in the western rock lobster fishery has remained below average for seven consecutive years (2006/2007–2012/2013), with 2008/2009 being the lowest in over 40 years. Examination of the timing of the start of spawning using fishery-independent data since the mid-2000s indicated that spawning has been occurring earlier. The low settlement appears related to higher water temperatures at the time of the onset of spawning (October) since the mid-2000s. Statistical analysis shows that the most (71%) of the variation in puerulus settlement was explained by the timing of spawning, storm activity during autumn/spring, and offshore water temperatures in February. Earlier spawning may cause a mismatch with other environmental factors such as peaks in ocean productivity and/or storms that assist the larvae return to the coast and offshore water temperatures that help the early stage larval growth. These variables produced a plausible hypothesis to explain the decline in puerulus settlement for these 7 years, including the recruitment failure of 2008/2009. They also predicted the substantial improvement in settlement for 2013/2014. Egg production levels did not to have a significant relationship with puerulus settlement levels after taking environmental variables into account. Further verification with additional years is required to see whether this relationship is maintained. Global climate change may influence these environmental factors: the timing of spawning is influenced by water temperature and there has been a reduced trend of autumn to spring storms off southwest Australia.